Existence and Ulam–Hyers stability results for Caputo–Hadamard fractional differential equations with non-instantaneous impulses - Mesfin Teshome Beyene; Mitiku Daba Firdi; Tamirat Temesgen Dufera (Boundary Value Problems)
Abstract In this manuscript, we investigated the existence, uniqueness, and Ulam–Hyers stability results of solutions to implicit Caputo–Hadamard fractional differential equations with noninstantaneous impulses and δ − d e r i v a t i v e $δ -derivative$ initial conditions. By employing Banach’s and Schaefer’s fixed-point theorems, we attain the required results. Finally, we provide examples that support the main findings we arrived at.